Social Media and its Impacts on the Morality of Muslim Youths in Kano Metropolis - Ibrahim Alhaji Isa (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Social media was started with the intent to create a forum to allow people from different social and cultural backgrounds to interact regardless of location and time, whereas youths are predominantly its users. They cannot imagine life without the Internet as they kept seeking for ways to connect virtually to everyone in the world. Social media have both positive and negative impacts on the youths, in which negative impacts on the moral development supersedes the positive impacts. Therefore, it becomes such a stumbling block to their moral development. It is on this ground that the study employed qualitative method through a critical analysis of Islamic scriptures and scholarly perspectives of both print and e-materials, by examining the concepts of youth, social media and its classification, as well as elaborate position and functions of youth in Islam. Moreover, the concept of morality in Islam is also expounded, ultimately, this research contributes in providing insights into how social media impact the moral development of Muslim youth as well as how their morality can be strengthened and preserved while using social media. It is concluded that, both government and the public have important roles to play in creating awareness on the dangers of social media and the ways the youth can have a good use of it as far as their moral development and being productive members of the society is concern.